Air pollution and human health risks: mechanisms and clinical manifestations of cardiovascular and respiratory diseases. (3rd April 2022) - Shahriyari, Habib Allah; Nikmanesh, Yousef; Jalali, Saeid; Tahery, Noorollah; Zhiani Fard, Akram; Hatamzadeh, Nasser; Zarea, Kourosh; Cheraghi, Maria; Mohammadi, Mohammad Javad
Abstract: Nowadays one of the main agents morbidity and mortality, in worldwide, is exposure to air pollution. Based on reported health organization, air pollution is the second most important factor in noncommunicable diseases (NCDs) and chronic diseases. The main source which has been found to exert harmful effects on human are particle matter (PM), Ozone (O3 ), nitrogen dioxide (NO2 ), sulfide dioxide (SO2 ), metals, and polyaromantic hydrocarbon (PAHs). The purpose of this review was the epidemiological literature on the health endpoint of exposure to air pollutants has on cardiovascular diseases (HACD) and respiratory diseases (HARD). About 1125 papers were retrieved according to various databases: Google Scholar, Science Direct, Web of Science, Springer, PubMed, and BMJ. Eighty papers based on abstract and article text were filtered. In the end after sieving, we selected 35 papers. The literature signs a notable undesirable effect from PM10, O3, NO2, SO2, metals, and PAHs emissions on cardiovascular and respiratory diseases. Results showed that air pollution has a significant contribution in the number of related cardiovascular diseases, respiratory diseases, and deaths. The survey requires the need to enact and enforce permissible PM10, O3, NO2, SO2, metals, and PAHs levels/standards for decrease in the health endpoint on human by relevant environmental authorities both at federal and state levels.